The Reality of Elementary School Science Teachers Use of Artificial Intelligence Applications in Teaching (The International Journal of Educational Sciences and Arts, 2024)
The current study targeted the honest researcher on using science teachers in the first stage in the Kingdom of Saudi Arabia to apply artificial intelligence in teaching. The model survey design was followed for the entire community, and an electronic questionnaire was designed that included 36 paragraphs distributed over three axes. The number of responses reached 71, which were analyzed using descriptive statistics. The results showed that the use of science teachers in the joint stage of artificial intelligence applications in teaching came to members and that most of the applications used in reading are read much more than those used in planning and evaluation. It also visualized teachers' perceptions of some obstacles to using artificial intelligence applications in teaching, represented in the weakness of technical professional differences among teachers. The study recommended the importance of intensifying professional development programs for teachers that develop technical skills and raise awareness, which further enhances the use of science teachers in the stage to practice artificial intelligence in teaching.
Keywords: Artificial Intelligence Applications; Primary Education; Science Teaching; Technical Competencies